The origin of (almost) everything - Lawton, Graham; Hawking, Stephen, 1942-2018. (London : John Murray Press, 2019)
A journey through life, the universe and everything. Introduction by Professor Stephen Hawking. When Edwin Hubble looked into his telescope in the 1920s, he was shocked to find that nearly all of the galaxies he could see through it were flying away from one another. If these galaxies had always been travelling, he reasoned, then they must, at some point, have been on top of one another. This discovery transformed the debate about one of the most fundamental questions of human existence - how did the universe begin? Every society has stories about the origin of the cosmos and its inhabitants, but now, with the power to peer into the early universe and deploy the knowledge gleaned from archaeology, geology, evolutionary biology and cosmology, we are closer than ever to understanding where it all came from. In The Origin of (Almost) Everything , New Scientist explores the modern origin stories of everything from the Big Bang, meteorites and dark energy, to dinosaurs, civilisation, timekeeping, belly-button fluff and beyond. From how complex life evolved on Earth, to the first written language, to how humans conquered space, The Origin of (Almost) Everything offers a unique history of the past, present and future of our universe.
Originally published: 2016.
"New Scientist."
Includes bibliographical references and index.
Keywords: Science -- Miscellanea; Curiosities and wonders -- Miscellanea; Life -- Origin